2009
DOI: 10.1007/s10826-009-9287-5
|View full text |Cite
|
Sign up to set email alerts
|

An International Assessment of the Emotional and Behavioral Strengths of Youth

Abstract: The assessment of emotional and behavioral strengths has been identified as an important part of the assessment process for children referred for specialized services. The Behavioral and Emotional Rating Scale-2 (BERS-2; Epstein, Behavioral and Emotional Rating Scale: a strength-based approach to assessment. PRO-Ed, Austin, TX, 2004) was developed as a standardized, normreferenced instrument to measure strengths of children and youth, and has been found to be a psychometrically sound instrument. We determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In the first study, Lappalainen et al (2009), found that the Finnish BERS-2 factor structure was similar to the original structure reported in the US and had acceptable internal consistency. In another study investigating reliability of the Finnish BERS-2 moderate to large correlations were reported between teachers and students and that higher agreement was achieved on externalizing than internalizing behaviors (Sointu et al forthcoming).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In the first study, Lappalainen et al (2009), found that the Finnish BERS-2 factor structure was similar to the original structure reported in the US and had acceptable internal consistency. In another study investigating reliability of the Finnish BERS-2 moderate to large correlations were reported between teachers and students and that higher agreement was achieved on externalizing than internalizing behaviors (Sointu et al forthcoming).…”
Section: Discussionmentioning
confidence: 74%
“…With the obvious need of strength-based assessment in Finland, the BERS-2 was translated into Finnish. Preliminary research by Lappalainen et al (2009) with a sample of 608 Finnish high school students replicated the original BERS-2 factor structure in the Finnish sample and reported acceptable internal consistency with Cronbach alphas ranging from .71 to .93. In another study of 275 Finnish fifth grade students, moderate to large cross informant agreement ranging from .35 to .51 were found between student and teacher BERS-2 assessments (Sointu et al forthcoming).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Collaboration with parents, especially those of children who have socio-emotional behaviour problems, should begin with an analysis of the child's strengths, which each and every child undoubtedly has. This may offer important assistance in reaching some of the parents who might otherwise be defensive and unwilling to co-operate (Epstein et al 2008;Lappalainen et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Researchers have particularly highlighted the critical role of socio-emotional development in school readiness and in accurate identification and interventions of children's socio-emotional competence for improving developmental outcomes and well-being (Chen 2006;Epstein et al 2008;Greenfiled, Iheoma and Munis 2004;Holland and Merrell 1998;Squires et al 2001). In Finland, there have been rising concerns for the early screening of the socio-emotional development of the child as well (Lappalainen et al 2009). The Finnish education system has three levels: basic education, comprising primary and lower secondary levels; upper secondary education and training; and higher education.…”
Section: Introductionmentioning
confidence: 99%